Guerrilla urbanism and digital production : a study of temporary occupation of public spaces - Lacroix, Igor (2018)
The paper presents some of the spatial production involved in three events promoted by different organizations in the city of Brasilia, Brazil. The role of architecture was to materialize sensations, experiences and phenomena for the people who participated. This production defines a kind of urbanism produced by groups of people who are temporarily using public spaces of the city with creativity. Limited by minimum time and budgets, and located in a place where high technology is scarce, handcraft is a necessity in all production processes. The main intention is to analyze how the use of advanced technology corresponds to this type of situation.